The Unknown Component Problem Theory and Applications - Villa, Tiziano; Yevtushenko, Nina.; Brayton, Robert K.; Mishchenko, Alan.; Petrenko, Alexandre; Sangiovanni-Vincentelli, Alberto; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
The Problem of the Unknown Component: Theory and Applications addresses the issue of designing a component that, combined with a known part of a system, conforms to an overall specification. The authors tackle this problem by solving abstract equations over a language. The most general solutions are studied when both synchronous and parallel composition operators are used. The abstract equations are specialized to languages associated with important classes of automata used for modeling systems. The book is a blend of theory and practice, which includes a description of a software package with applications to sequential synthesis of finite state machines. Specific topologies interconnecting the components, exact and heuristic techniques, and optimization scenarios are studied. Finally the scope is enlarged to domains like testing, supervisory control, game theory and synthesis for special omega languages. The authors present original results of the authors along with an overview of existing ones.
1. Synopsis -- 2. Equations over Languages and Finate Automata -- 3. Equations over Finite State Machines -- 4. Equations Over w-Automata -- 5. A Survey of Relevant Literature -- 6. Implementation of Automata Manipulations -- 7. Manipulations of FSMs Represented as Sequential Circuits -- 8. The Software Package BALM -- 9. Fundamental Operations in BALM -- 10. Computation of Flexibility in Sequential Networks -- 11. Computation of Sequential Flexibility in Netlists by Windowing -- 12. Computation of Sequential Flexibility in Networks of FSMs by Windowing -- 13. Language Solving Using Simulation Relations -- 14. Exploitation of Flexibility in Sequential Networks -- 15. Supervisory Control -- 16. Testing -- 17. Synthesis of Strategies for Games -- 18. Extending BALM to Synchronous Equations Over co-Büchi Specifications -- 19. Conclusions and Open Problems.
Keywords: Engineering; Logic design; Computer engineering; Systems engineering; Engineering; Circuits and Systems; Logic Design; Electrical Engineering